Investigating the asymmetric impact of energy consumption on reshaping future energy policy and economic growth in Iran using extended Cobb-Douglas production function. (1st February 2021) - Oryani, Bahareh; Koo, Yoonmo; Rezania, Shahabaldin; Shafiee, Afsaneh
Abstract: This study scrutinised the symmetric/asymmetric impact of energy consumption on the economic growth (RGDP) of Iran in the framework of the extended Cobb-Douglas production function from 1970 to 2017. The linear and nonlinear Autoregressive Distributed Lag (ARDL) confirmed that a positive and negative shock on energy consumption had the same impact on RGDP. The empirically obtained outcomes supported confirmed the positive impact of energy consumption and capital stock on GDP in both the short and long terms. The opposite was true for CO2 emissions and labour force. The results of a Toda Yamamato (T-Y) test showed bidirectional causality between CO2 emissions and energy consumption. Moreover, CO2 emissions and energy consumption exhibited a causality effect on economic growth. Furthermore, residual diagnostic/model stability tests and sensitivity analyses based on Fully Modified Ordinary Least Squares (FM-OLS) and Dynamic Ordinary Least Squares (DOLS) verified the perfectness and robustness of the results obtained from the ARDL model, respectively. Based on the growth-enhancing and environment-degrading effects of energy consumption, switching from conventional energy to renewable energy must be considered in national energy policies. Appropriate policy implications were recommended under two categories: market-based interventions (both directly and indirectly) and non-market-based interventions. Highlights: The asymmetric impact of energy consumption on economic growth of Iran were studied. The Toda Yamamato causality test was applied to check the causal relationship. The symmetric impact of energy consumption on GDP was confirmed. The one-way causality running from EC and CO2 emissions to GDP was verified. The market-based and nonmarket-based interventions were recommended.